Development Plan of Village Sandhir on the Basis of PRA Techniques - R.P.Singh, (Journal of Agricultural Extension Management, 2025)
Our country has got a most valuable and most sustainable social system in the world. The reason for this situation is that more than 80% population of this country lives in villages, and the roots of traditional, social, religious and spiritual system are very deeper in the rural communities. Any change that occurs in Indian society, the rural people are the latest people to be affected. Since the means of communication are not very much effective in rural societies, the information reaches very late in villages and rural India